Isolated systolic arterial hypertension - L. G. Ratova; I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2007)
The review focuses on various aspects of isolated systolic arterial hypertension (ISAH). Main principles of ISAH diagnostics and treatment in the elderly are presented.